Superação da dormência em sementes de Murdannia nudiflora (L.) Brenan - Erasmo, Eduardo Andrea Lemus; Terra, Marcelo Alves; Domingos, Vanessa David; Martins, Cibele Chalita [UNESP]; da Costa, Neumárcio Vilanova (Universidade Estadual de Maringa, 2008)
The objective of this study was to identify treatments capable of promoting and standardizing the germination of Murdannia nudiflora (L.) Brenan seeds. The seeds of this weed were submitted to the following treatments: mechanical abrasion with 220-grit sandpaper (20, 30 and 40 frictions); immersion in sulfuric acid (90% for 30 and 40 seconds), followed by washing in running water; immersion in sodium hypochlorite (2.5% for 8 and 12 hours) and lye (5 minutes), followed by five washings in distilled water; immersion in KNO 3 (1% for 24 hours); preheating at 40°C in a humid or dry substrate for 2, 3 and 4 weeks. The statistical design was totally randomized, with four repetitions. The number of germinated seeds was counted every other day. The most favorable treatments were preheating at 40°C in humid substrate for 3 weeks, followed by mechanical abrasion after 40 frictions and immersion in sulfuric acid for 40 seconds.
Overcoming seed dormancy in Murdannia nudiflora (L.) Brenan
Keywords: Commelinaceae; Germination; Weed; Murdannia nudiflora